2019
DOI: 10.1016/s0140-6736(18)32995-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting sex-related reporting in medical research: a cross-disciplinary bibliometric analysis

Abstract: Background Clinical and preclinical studies have shown that there are sex-based differences at the genetic, cellular, biochemical, and physiological levels. Despite this, numerous studies have shown poor levels of inclusion of female populations into medical research. These disparities in sex inclusion in research are further complicated by the absence of sufficient reporting and analysis by sex of study populations. Disparities in the inclusion of the sexes in medical research substantially reduce the utility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
179
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(196 citation statements)
references
References 40 publications
6
179
0
3
Order By: Relevance
“…In oncological research, for example, several sex‐based differences in the treatment and outcomes of cancer patients have been explored and revealed important issues in, for example, drug responses and toxicity . The presence of a female author in a study has been positively associated with the likelihood of the exploration and analysis of these sex‐based differences . Diversity in sex of researchers could therefore also contribute to a more diverse perception of science, possibly contributing to favorable outcomes for patients in the end, especially in the light of recent findings in sex‐based differences in oncology …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In oncological research, for example, several sex‐based differences in the treatment and outcomes of cancer patients have been explored and revealed important issues in, for example, drug responses and toxicity . The presence of a female author in a study has been positively associated with the likelihood of the exploration and analysis of these sex‐based differences . Diversity in sex of researchers could therefore also contribute to a more diverse perception of science, possibly contributing to favorable outcomes for patients in the end, especially in the light of recent findings in sex‐based differences in oncology …”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] The presence of a female author in a study has been positively associated with the likelihood of the exploration and analysis of these sex-based differences. 39,40 Diversity in sex of researchers could therefore also contribute to a more diverse perception of science, possibly contributing to favorable outcomes for patients in the end, especially in the light of recent findings in sex-based differences in oncology. 36 Our study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the NIH prompts and continually mounting evidence identifying clinically important sex and gender differences in disease, pharmacology, therapeutic interventions, and medical outcomes, the earnest inclusion of the variables of sex and gender into mainstream medical research and clinical care has been slow to occur. As many sex‐ and gender‐based medicine (SGBM) principles are directly related to acute care, we, as leaders of Sex and Gender in Emergency Medicine (SGEM) Interest Group at SAEM, identified a need to accelerate education surrounding SGBM within academic emergency medicine (EM) . This innovation paper describes how a Jeopardy‐like game may facilitate knowledge translation of SGBM principles to academic emergency physicians (EPs) to enhance their use in clinical care, teaching, and research.…”
Section: Need For Innovationmentioning
confidence: 99%
“…It matters to science. More gender‐diverse and inclusive teams improve outcomes in science and medicine . It matters to patients.…”
mentioning
confidence: 99%
“…More gender-diverse and inclusive teams improve outcomes in science and medicine. [2][3][4] It matters to patients. A Florida study found female patients with acute myocardial infarction were more likely to survive if they were treated by female than by male doctors.…”
mentioning
confidence: 99%